PERAN MEDIASI MODERASI BURNOUT DAN PSYCHOLOGICAL CAPITAL PADA PENINGKATAN JOB PERFORMANCE - Irma Fahmi; Fauji Sanusi; Muljadi Muljadi (Ekonomi dan Bisnis: Berkala Publikasi Gagasan Konseptual, Hasil Penelitian, Kajian, dan Terapan Teori, 2023)
This study aims to explore and analyze the impact of emotional intelligence and employee engagement on job performance, with psychological capital and burnout as moderation. A descriptive quantitative method with a causal perspective is used in this investigation. A sample of 110 respondents was employed for the research theme on employees at PT. Luhai Industrial Cikande Serang. The questionnaire's responses were scored on a scale from 1 to 10. Data was processed and evaluated using SmartPLS version 3.29. The findings of this research shown 1). Emotional intelligence does not significantly affect job performance. 2). Employee engagement has a huge positive impact on job performance. 3). Emotional intelligence has a large positive effect on psychological capital. 4). Psychological capital has a large positive effect on job performance. 5). Psychological capital can mediate the impact of emotional intelligence on job performance. 6). Burnout strengthens the relationship between employee engagement and job performance. 7). Burnout weakens the relationship between psychological capital and job performance.